2022
DOI: 10.1155/2022/8920861
|View full text |Cite|
|
Sign up to set email alerts
|

Heme Oxygenase-1 Inhibits the Proliferation of Hepatic Stellate Cells by Activating PPARγ and Suppressing NF-κB

Abstract: Background. Hepatic stellate cells (HSCs) are reported to play significant roles in the development of liver fibrosis. Heme oxygenase-1 (HO-1) is a key rate-limiting enzyme, which could decrease collagen synthesis and liver damage. Nevertheless, it was yet elusive towards the function and mechanism of HO-1. Methods. An HO-1 inducer Hemin or an HO-1 inhibitor ZnPP-IX was used to treat the activated HSC-T6, respectively. MTT assay was adopted to detect cell proliferation. Immunocytochemical staining was employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The up-regulation of HO-1 could protect the liver against inflammation via its products, CO, and biliverdin [ 29 ]. Recent studies proved that HO-1 induction could inhibit hepatic stellate cell proliferation [ 30 ] and, as a result, the expression of -SMA decreased, as was shown in our study too.…”
Section: Discussionsupporting
confidence: 89%
“…The up-regulation of HO-1 could protect the liver against inflammation via its products, CO, and biliverdin [ 29 ]. Recent studies proved that HO-1 induction could inhibit hepatic stellate cell proliferation [ 30 ] and, as a result, the expression of -SMA decreased, as was shown in our study too.…”
Section: Discussionsupporting
confidence: 89%
“…Other reasons may include induction of anti-inflammatory molecules. The trend toward enhanced mRNA expression of HO-1 was observed by G2-SUISO administration (data not shown) and several studies demonstrated that HO-1 inhibit NF-κB 29 31 .…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the activation of HO-1 was considered to be essential for the anti-in ammatory effect of PPAR-γ, and the interaction between HO-1 and PPAR-γ was also proved [23]. Hui Yang's study also indicated that the activation and expression of HO-1 could increase the expression of PPAR-γ; that is, the expression level of PPAR-γ would change with the change of the expression level of HO-1 [24]. This is consistent with our results that PPAR-γ and HO-1 can regulate and in uence each other.…”
Section: Discussionmentioning
confidence: 96%